1993
DOI: 10.1121/1.408131
|View full text |Cite
|
Sign up to set email alerts
|

A T matrix for scattering from a doubly infinite fluid–solid interface with doubly periodic surface roughness

Abstract: The T-matrix formalism is used to calculate scattering of a plane wave from a doubly infinite fluid–solid interface with doubly periodic surface roughness. The Helmholtz–Kirchhoff integral equations are used to represent the scattered pressure field in the fluid and the displacement field in the solid. The boundary conditions are applied and a system of four coupled integral equations is obtained. The incident and scattered pressure fields in the fluid, as well as the surface pressure field, are represented by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The third one is the paper by Bishop and Smith [5], in which research is reported on the diffraction on quite the same corrugated surfaces as is undertaken in the present paper. However, Bishop and Smith [5] use a different method which consists of a ÔT-matrixÕ formalism applying the Helmholtz-Kirchoff integral equations to represent the scattered pressure field in the liquid and the displacement field in the solid.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…The third one is the paper by Bishop and Smith [5], in which research is reported on the diffraction on quite the same corrugated surfaces as is undertaken in the present paper. However, Bishop and Smith [5] use a different method which consists of a ÔT-matrixÕ formalism applying the Helmholtz-Kirchoff integral equations to represent the scattered pressure field in the liquid and the displacement field in the solid.…”
Section: Introductionmentioning
confidence: 89%
“…Another reason is because it can also be found in an earlier paper of Mampaert and co-workers [9], in which a similar approach is formulated as in the present paper, that for a singly corrugated surface, the shape of the corrugation is indeed relatively unimportant and has no effect at all on the position of anomalies in the reflection spectra. Furthermore, even though Bishop and Smith [5] observe some anomalies in their reflection spectra, they do not prove what exactly causes these anomalies, which could be done, for example, by means of depicting the displacement field of the diffracted sound. Finally, Bishop and Smith [5] apparently have not found any situation under which a reflection or transmission coefficient exceeds unity.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations